Hypertension: comparison of self-reported information and objective measures from the first Portuguese National Health Examination Survey (INSEF) - Kislaya, Irina (2017)
This study compares self-reported and examination-based prevalence of hypertension using data from the Portuguese National Health Examination Survey (n=4911), that combines personal interview and clinical measurements. Logistic regression was used to identify factors associated to incorrect self-reports. Self-reports underestimated prevalence of hypertension. The accuracy of self-reports varied between population subgroups. Sex, age group, education and use of healthcare services were associated with incorrect self-reports of hypertension. Adding objective measurements to self-reported questionnaire improve data accuracy and allow better understanding of socioeconomic inequalities in health.